PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA VARIO DI KECAMATAN GEBOG KUDUS - Yunus Saputra, 09.05.51.0112; Sutedjo, Bambang (Students Journal of Economic and Management, 2014)
The purpose of this study is to examine and analyze the effect of the product, brand image and purchase decisions. The population in this study is the consumer who has the Honda Vario motorcycle brand in the District Gebog, Kudus. The samples in this study were as many as 100 customers. The sampling technique using accidental sampling. Data collection techniques used were primary analysis technique used is multiple regression. The results showed that: (1). Quality products and a significant positive influence on purchasing decisions. (2). Brand image and a significant positive influence on purchasing decisions. (3). Promotion of positive and significant influence on purchasing decision Keywords: Product Quality, Brand Image, Promotion, Purchasing Decision